SPLICING FACTOR1 Is Important in Chloroplast Development under Cold Stress. Issue 2 (30th July 2020) - Zhu, Yajuan; Wu, Wenjuan; Shao, Wei; Chen, Jingli; Shi, Xiaoning; Ma, Xiaoyu; Xu, Yong-Zhen; Huang, Weihua; Huang, Jirong
Abstract: Intron splicing efficiency regulated by SPLICING FACTOR1 is important for chloroplast development under cold stress in Arabidopsis. Abstract: RNA SPLICING FACTOR1 (SF1) is responsible for recognizing the branch point site (BPS) sequence in introns and is critical for pre-mRNA splicing. In Arabidopsis ( Arabidopsis thaliana ), splicing factor1 (AtSF1) has been shown to retain the conserved function, but it is unexpected that null atsf1 mutants are viable. Here, we identified an allele of atsf1, named suppressor of thf1-4 ( sot4 ), from suppressor screening for leaf variegation of thylakoid formation1 . The sot4 mutant resulting from the G-to-R mutation at the highly conserved 198th amino acid residue within the functionally unknown domain exhibits leaf virescence associated with less accumulation of mature plastid ribosomal RNA, particularly under cold stress. Interestingly, the same point mutation in yeast Saccharomyces cerevisiae MUD synthetic-lethal 5p (SF1/Msl5p) also causes hypersensitivity to coldness and a low splicing activity for the introns with suboptimal BPS sequences. Transcriptomic profiling and reverse-transcription quantitative PCR analyses showed that expression of many genes were up- or downregulated in atsf1 via insufficient intron splicing. Our search for a BPS consensus from the retained introns in atsf1 transcriptomes, combined with RNA electrophoresis mobility shift assays, revealed that AtSF1 directly binds to the BPS consensus containing 5′-CU(U/A)AU-3′. Taken together, our data provide insight into a role for AtSF1 in regulating intron splicing efficiency, which helps plants acclimate to coldness.